How i learned to stop worrying and love the crisis - Jan Fidrmuc; Ariane Tichit (Center for Economic Studies and ifo Institute (CESifo), 2012)
We investigate the effects of economic crises on the subsequent economic performance, economic reform, democratization and institutional change. Our analysis is based on a sample of post-communist countries, most of which experienced severe economic crises during the 1990s. We find that the severity of crisis has had a positive impact on the subsequent pace of economic reform, economic growth and, with a delay, on investment and institutional change. Episode of high inflation, moreover, translate into lower subsequent inflation. Crises thus appear to serve as catalysts of reform and institutional change and lead to better long-term economic performance.
Keywords: O11; O47; P27; 330; crisis; transition; growth; inflation; reform; institutions; Wirtschaftskrise; Übergangswirtschaft; Wirtschaftsreform; Institutioneller Wandel; Demokratisierung; Wirkungsanalyse; Wirtschaftswachstum; Transformationsstaaten